(untitled) (Annals of Medical Research, 2022)
Aim: In this study, we evaluated the effects of delivery time on maternal-fetal outcomes by evaluating patients who were taken to the gynecological intermediate intensive care unit according to their delivery hours. Materials and Methods: This study cohort included 292 women aged 18-45 years, whom we followed up in the postpartum gynecological intermediate intensive care unit. We divided the patients into three groups according to the time they gave birth. Those who gave birth between 08:00-16.00 formed group1, those who gave birth between 16:00-24:00 group2, and those who gave birth between 24:00-08:00 formed group 3. We compared all collected data between groups. Result: Hysterectomy (45(36%)) and blood transfusion (35(28%)) rates in the first group were higher than the other groups (p <0.001). Drain placement rates were higher in group 3 (48 (84.2%), p<0.001). No other operative approach and complications were significantly different between the three groups. Conclusion: Regarding maternal-fetal outcomes and surgical complications, making the delivery outside of working hours or after 24:00 may not have a negative effect.